Express “ln va “ as a product
Solution:
==================================================================
from x^a/b = r(b) [x^a], where r = root, and r(b) = root of index b; a = exponent
==================================================================
from our example: va...

7x+10=5x-3, Solution x=-13/2 or x= -5 3/2
Step by step Solution: step 1: re agruping similar terms
(a)sdd -5x the whole equation
-5x+7x+10=-5x+5x-3 ==>2x+10=-3
(b) add -10 the whole equation
2x+10=-3 ==> -10+2x+10=-10-3 ==> 2x=-13
step...

-9(x - 5) = x + 22 1/2, solution x=45/20 or x=2 1/4 step by step solution: step 1: change mix fraction to a pure fraction, 22 1/2 = [(22*2)+1]/2 =45/2 then -9(x - 5) = x + 22 1/2 ==> -9(x - 5) = x + 45/2 step 2: multiply the whole equation by 2, that is to write the equation without...

-(5x+2)+2(1+5x)
Math use compact notation and your question is about one of them.
-(5x+2)= -1*(5x+2) = -1*5x+-1*2 = -5x-2
note that if we have -5x-2 you can factor a negative sign or a -1 out ant it convert in -(5x+2)so (-5x-2 = -1*(5x+2) = -(5x+2)
====================================================================
2(1+5x)...

The Standart for is: Ax+By = C
y= 1/2 + 3, I thing that you missing some variable that could be called "x" or "z"
you expression could be writen y=x/2+3 or y= 1/2 +3x or y=x/2 + 3z, I do not know.
To solve it
step 1: re write the equation...

133=-7(1-4k)
Step by Step solution:
Step 1:multiply by 1/-7 the whole equation
(1/-7)[133] = (1/-7)[-7(1-4k)] ==> 133/-7 = (1-4k) ==> -19 = (1-4k)
Step 2: add -1 the whole equation
-19-1 = -1+1 -4k ==> -20= -4k
Step 3: multiply by (1/-4) the whole equation
(1/-4)(-20)=...

133=-7(1-4k)
Step by Step solution:
Step 1:multiply by 1/-7 the whole equation
(1/-7)[133] = (1/-7)[-7(1-4k)] ==> 133/-7 = (1-4k) ==> -19 = (1-4k)
Step 2: add -1 the whole equation
-19-1 = -1+1 -4k ==> -20= -4k
Step 3: multiply by (1/-4) the whole equation
(1/-4)(-20)=...

Data: x+y=16 and x-y=0 ==> x=y
==============================================================
I going to substitude x on y, because x=y
Substituing:
x+y=16 ==> x+x=16 ==> 2x=16 ==> x=16/2 ==> x=8
=============================================================
Pruve:
x+y=16
if x=y and x=8, then y=8
subtituing...

Data: for (x,y) => A(1) = (6,9); A(2)=(-3,9)
Def: slope = [y(2)-y(1)]/[(x(2)-x(1)], to obtain the slope you can chose as point 1 or 2 the A(1) or A(2) coordinate.
if point y(1)=y(2), then y(2)-y(1)=0 and your slope should be 0, if and only if x(1)=/= x(2), if...

1.2(x-2)=2-x; Solution: x=2 ============================================================================ Step by Step solution 1.2(x-2)=2-x
Step 1: Multiply by 1.2 all in the parentesis. That is the distribution property.
1.2x-2.4=2-x,
Step 2: Reagruping equal terms
(1)add +x...

Data: (x,y) = (-6,-4), then x = -6, y = -4; m = 5 (slope)
the General line equation is: y = mx + b, where m=slope, and b = y intersept or the point of the line where x=0, and y cut the y axis
==================================================================
y=mx+b, from...

5/2x-4/x^2=7/2x^2, Solution: x=3
Step by Step
multiply by 4x^2 the whole expression. It is because 4x^2 is the common denominator between 2x,x,and 2x^2. To add fraccion they have to have common denominator.
4x^2[5/2x-4/x^2] = 4x^2[7/2x^2] ==>
10x-16=14 ==>
10x=14+16...

y = sin x
dy/dx = y'(x)
then y'(x)= cos (x) ======================================================================== Prove: ========================================================================= [1] Definition of sin (x) = [e^(xi)-e(-xi)] / 2 [2] y'(x)= y'(e^xi)/2 - y'(e^-xi)/2...

2x^(5/3)+64=0
Solution
2x5/3+64=0
x^(5/3) = -64/2
x^(5/3) = -32
x^5 = -32^3
x^5 = -32768
x = (-32768)^(1/5)
x = (32768)^(1/5) i, where i = (-1)^(1/2)
x=8i
===========================================================================
Step by Step solution
Our goald is to write an equation with a form...